PENERAPAN NILAI ETIKA SOPAN SANTUN DALAM PEMBELAJARAN BAHASA INDONESIA PADA SISWA KELAS IVB SD NEGERI 94 BEBA - Idfa Luth Fika Adha; Muvida Mansyur; Iskandar; ST Hasiah (STKIP Subang, 2025)
This study aims to examine the ethics and manners of fourth-grade students during learning activities. The research used in this study is Classroom Action Research (CAR) or often called classroom action research (PTK). This study aims to examine the ethics and manners of fourth-grade students during Indonesian language learning activities. The subjects in this study were classroom learning activities. Data collection techniques were carried out by providing questionnaires, class observations, teacher interviews, and supported by documentation. The results of the study revealed that some fourth-grade students of SD Negeri 94 Beba still lacked in the application of ethical manners. They were still often noisy when the teacher explained the material in front of the class and there were still some students who sometimes denied the advice given by the teacher. Things that happened in this school were certainly caused by influencing factors, such as family factors, the environment, playmates and the like. Schools and teachers have done their best to teach ethical manners in behavior, speech, and clothing, but the results are less than optimal, because students are only in the school environment for a few hours a day, the rest of the time students carry out their activities outside the school environment, which results in what has been taught by teachers regarding ethical manners being disturbed by the ethical manners that exist outside the school environment.